Features of low-temperature exciton dynamics in J-aggregates with topological disorder - Malyukin, Yu.V.; Katrich, G.S.; Efimova, S.L.; Sorokin, A.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
It is shown on the basis of an analysis of the J-band shape, luminescence spectra, and luminescence decay that self-trapping of excitons takes place in J-aggregates with strong topological disorder. A self-trapping barrier must be overcome for this to occur. A microscopic model of the self-trapped state is presented.